2019
DOI: 10.1002/1348-9585.12065
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes for facilitators of workplace environment improvement applying a participatory approach

Abstract: Objectives The purpose of this study was to determine changes in awareness, behavior, and relationships among facilitators who were involved in facilitating the conduct of the participatory workplace improvement program and to examine the facilitators' outcomes as a result of their active involvement in the program. The outcome components were also examined in relationship to their associations with various factors. Methods An anonymous self‐administered questionnaire survey was conducted for 83 facilitators. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In this sense, the following external determinants can be identified: macrocontextual factors, related to policies and systems of legal regulation of occupational health [28,29], such as the capacity of representatives and workers to paralyze productive activity in the face of serious or imminent risk [30]; the promotion of regulations that reward the integration of the prevention management system through its own means to facilitate participation [31]; the promotion of participation through the requirements of the labour inspection [32], regulations that do not systematically make technicians responsible for the prevention of accidents in companies to prevent expert knowledge from blocking participation [33]; or the promotion of policies for the representation of interests that facilitate decentralised self-regulation through the participation of autonomous trade unions [27,34]. The internal factors that influence the effectiveness of participation are business leadership and willingness to promote a participatory culture [35][36][37][38][39][40]; training and empowerment of workers and their representatives to collectively challenge unsafe situations [37][38][39]; the size of the workplace and the sector of activity to the extent that participation is greater in larger workplaces and in industries where occupational risks are more evident [18,27,41]; in addition, greater capacity for participation will exist when specialized occupational health representation is unionized [42] or has strong external support from the union [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the following external determinants can be identified: macrocontextual factors, related to policies and systems of legal regulation of occupational health [28,29], such as the capacity of representatives and workers to paralyze productive activity in the face of serious or imminent risk [30]; the promotion of regulations that reward the integration of the prevention management system through its own means to facilitate participation [31]; the promotion of participation through the requirements of the labour inspection [32], regulations that do not systematically make technicians responsible for the prevention of accidents in companies to prevent expert knowledge from blocking participation [33]; or the promotion of policies for the representation of interests that facilitate decentralised self-regulation through the participation of autonomous trade unions [27,34]. The internal factors that influence the effectiveness of participation are business leadership and willingness to promote a participatory culture [35][36][37][38][39][40]; training and empowerment of workers and their representatives to collectively challenge unsafe situations [37][38][39]; the size of the workplace and the sector of activity to the extent that participation is greater in larger workplaces and in industries where occupational risks are more evident [18,27,41]; in addition, greater capacity for participation will exist when specialized occupational health representation is unionized [42] or has strong external support from the union [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…They found that teams that had developed action plans through an employee's active participation exhibited a larger increase in workplace social capital than did other teams 48) . This participatory style of program was also identified as an effective and practical method for promoting comprehensive risk management among both workers and employers 49) . Offering a workplace improvement program, in which an individual teacher actively participates in the planning process, should be considered to foster a cohesive workplace environment and the consequent positive mental health among individual teachers.…”
Section: Discussionmentioning
confidence: 99%
“…SWING identifies workplace-improvement needs from the workers' perspective, providing valuable information for establishing a participatory work improvement that promotes occupational safety and health and comprehensive risk management for both workers and employers [23]. Thus, we believe that the rich data provided by SWING can help promote occupational safety, health, and management.…”
Section: Swing's Expected Contributions To Occupational Health Theore...mentioning
confidence: 96%